India - Hyderabad - ICRISAT - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and their Gene Bank. Photo: P. Casier (CGIAR). Please creadit appropriately.